Fostering environmental, social and governance-oriented startups: Accessing the moderating effect of universities on entrepreneurial leadership - Ajabnoor, Nouran (Edelweiss Applied Science and Technology, 2024)
This study explores the complex factors influencing the achievement of Environmental, Social and Governance (ESG) companies. This study examines the impact of several antecedents such as Entrepreneurial Leadership Programs (ELP), Incubator and Accelerator Support (IAS), Access to Mentorship and Network Opportunities (AMNO) and Availability of Funds and Financial Resources (AFFR) on the development of ESG startups drawing upon the theoretical framework of Resource-Based View (RBV). A cross-sectional survey design was used to collect data from academic institutions in Saudi Arabia including state and private universities. Three public and private universities from various geographic locations were chosen for this study. The results suggest a favorable relationship between ELP and the establishment of ESG startups. This highlights the significance of education and the cultivation of skills in fostering entrepreneurial endeavours. The analysis revealed no statistically significant relationship between IAS and ESG startup performance. However, a positive relationship between AMNO and the establishment of ESG startups underscoring the importance of networking and mentorship was found. The research findings also indicate universities’ substantial influence in shaping these associations highlighting the need for additional exploration of the factors that motivate university participation in ESG entrepreneurship. The findings significantly contribute to the overall comprehension of the elements and interactions that impact the growth of ESG startups. Moreover, they offer vital insights for policymakers and practitioners involved in the realm of socially responsible entrepreneurship.